Thoracic patterning by the Drosophila gap gene hunchback. - Wu, X.; Vasisht, V.; Kosman, D.; Reinitz, J.; Small, S. (Developmental Biology, 2001)
Localized gene expression patterns are critical for establishing body plans in all multicellular animals. In Drosophila, the gap gene hunchback (hb) is expressed in a dynamic pattern in anterior regions of the embryo. Hb protein is first detected as a shallow maternal gradient that prevents expression of posterior gap genes in anterior regions. hb mRNA is also expressed zygotically, first as a broad anterior domain controlled by the Bicoid (Bcd) morphogen, and then in a stripe at the position of parasegment 4 (PS4). Here, we show that the PS4-hb stripe changes the profile of the anterior Hb gradient by generating a localized peak of protein that persists until after the broad domain has started to decline. This peak is required specifically for the formation of the mesothoracic (T2) segment. At the molecular level, the PS4-hb stripe is critical for activation of the homeotic gene Antennapedia, but does not affect a gradient of Hb repressive activity formed by the combination of maternal and Bcd-dependent Hb. The repressive gradient is critical for establishing the positions of several target genes, including the gap genes Kruppel (Kr), knirps (kni), and giant (gt), and the homeotic gene Ultrabithorax (Ubx). Different Hb concentrations are sufficient for repression of gt, kni, and Ubx, but a very high level of Hb, or a combinatorial mechanism, is required for repression of Kr. These results suggest that the individual phases of hb transcription, which overlap temporally and spatially, contribute specific patterning functions in early embryogenesis.